1969
DOI: 10.4294/jpe1952.17.77
|View full text |Cite
|
Sign up to set email alerts
|

Explosion Seismic Studies of the Underground Structure in the Matsushiro Earthquake Swarm Area

Abstract: The underground structure in the Matsushiro Earthquake Swarm Area was derived from the data of explosion seismic observations in profiles A and B. First, the number of layers and the velocity in each layer are determined by using the T' curve. Then on the assumption that the dip of each interface is small, the structure of the first approximation was derived. The final models were derived by the method of trials and errors so as to reduce (O-C), the difference between observed and calculated travel times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 2 publications
2
18
0
1
Order By: Relevance
“…All events located in this paper occurred in the upper part of the layer of VP= 6.1 km/s; similar phenomena were reported for the Matsushiro Earthquake Swarm Area (ASANO et al, 1969), the Tohoku District (TAKAGI et al, 1977), and the Izu Peninsula (ASANO et al, 1982). MFH: Magnitude determined by FMO (1982).…”
Section: Seismic Activities and Focal Parameters For Shallow Eventssupporting
confidence: 84%
“…All events located in this paper occurred in the upper part of the layer of VP= 6.1 km/s; similar phenomena were reported for the Matsushiro Earthquake Swarm Area (ASANO et al, 1969), the Tohoku District (TAKAGI et al, 1977), and the Izu Peninsula (ASANO et al, 1982). MFH: Magnitude determined by FMO (1982).…”
Section: Seismic Activities and Focal Parameters For Shallow Eventssupporting
confidence: 84%
“…This profile crosses the Matsushiro earthquake swarm area and this forms an extensional profile of the 1957 experiment by ASANO et al (1969). We found a large buried fault in the middle of the profile, which is probably a reverse fault.…”
Section: Introductionsupporting
confidence: 54%
“…This kind of experiment was conducted in the Matsushiro Earthquake Swarm area, Central Japan in 1967 for the first time (ASANO et al, 1969a(ASANO et al, , b, c, 1973. The information on the crustal structure in the region around Matsushiro derived from explosion seismic data was really valuable to investigate into the real cause of earthquake swarm.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed studies on the crustal structure by the seismic refraction method in the Matsushiro Earthquake Swarm area, Central Japan in 1967 give one example. The results of the detailed studies showed that earthquakes took place within the granitic layer, a fault-like structure or an offset in the upper boundary of the granitic layer was derived near the most active area, the anomalous portion with low velocity and low Q was found in the granitic layer within the most active area and so forth (ASANO et al, 1969a(ASANO et al, , b, c, 1973OKADA et al, 1970;SUZUKI, 1972).…”
mentioning
confidence: 99%